INSIDEN PENURUNAN BANNER PEOPLE’S JUSTICE DI DOCUMENTA FIFTEEN DAN PERINTANG KOMUNIKASI ANTARBUDAYA - Heron, Heronimus; Kim, Min Seong (UI Scholars Hub, 2024)
On June 20 2022, artists and art observers in Indonesia were shocked by the circulation of information that the People's Justice banner by Taring Padi exhibited at Documenta Fifteen interpreted as containing elements of antisemitism. Taring Padi explained that the People's Justice banner was based on the political history of Indonesia under New Order regime and had nothing to do with antisemitism, however, the banner was eventually dismantled on June 21, 2022. Based on this background, there are several research questions to explore: How is the chronology of dismantling the People's Justice banner at Documenta Fifteen? Why did this incident occur? What does Taring Padi need to do as a cultural agency? This research uses qualitative research methods with a critical discourse analysis approach. The results of this research found that the protests against two figures in the People's Justice banner due to two reasons: firstly, the unwillingness of the protesting parties to ask Taring Padi for confirmation and listen to Taring Padi's explanation. Secondly, Taring Padi's ignorance regarding practices considered antisemitism because knowledge about the history of antisemitism is uncommon in Indonesia. The People's Justice banner can be a medium for dialogue between fellow artists and the audience. However, this work has potential weaknesses because it depicts a gap in antagonism that narrows the interpretive space. This potential can be anticipated if the artist opens up a space for interpretation and the audience must be open, so that discursive encounters can be held to understand shared culture and social problems.